Measuring the efficiency of tourism sector in Sri Lanka: An extension of the method to stochastic frontier analysis - Mufeet, Musthapha; Mubarak, Kaldeen; Nusrathali, Noordeen (The journal of contemporary issues in business and government, 2021)
The research was conducted to examine the performance of Sri Lanka's tourism industry. Secondary data was obtained from the annual reports of the Sri Lanka Tourism Development Authority. The inefficiency in tourist arrival, total annual receipts and per day receipt from a tourist were estimated using Stochastic Frontier Analysis (SFA) between the periods from 1970 to 2019. And the factors influencing on the above tree inefficiencies were estimated combined with Cobb–Douglas frontier function under the assumption of half-normal distribution. The study found that the efficiencies were 86.2 %, 78.4 %, and 89.6 % respectively in tourist arrival, tourist receipts and per day receipts. The productivity of both the number of tourist arrivals and the overall reception of tourists was significantly (p<0.05) increased by the number of indirect jobs involved in tourism activities and the number of beds available for accommodation. Tourist arrival inefficiency could be substantially (p<0.05) improved by embarkation tax. Similarly, the number of international conferences held in BMICH significantly (p<0.05) had a negative impacted on the inefficiency of Sri Lanka's tourist arrival and tourism receipts. The present study revealed that growing investment in conference halls will create an opportunity to start more international conferences and symposiums to increase the efficiency of the tourism industry in Sri Lanka instead of investing more in rooms and direct recruitment to the tourism sector.